GAMIFICATION-BASED ASSESSMENT: THE WASHBACK EFFECT OF QUIZIZZ ON STUDENTS’ LEARNING IN HIGHER EDUCATION - Pitoyo, Muhammad Dafit; Sumardi, Sumardi; Asib, Abdul (International Journal of Language Education, 2020)
Abstract Assessment and technology are two components that are very important in education. Assessment is the core of education which provides teachers lots information from their students and technology helps to achieve the learning goal more easily. Teachers are able to take the advantages of the integration of technology and assessment to get really detail information of students test to create a good teaching process. However, there are not many teachers who really consider about assessment and the washback effect on students? learning. Thus, this study aimed to know the washback effect of Quizizz assessment platform on students? learning. To investigate the issue, the researcher used questionnaire, observation and in-depth interview. The data which obtained would be analyzed qualitatively. The result of the study shows that students were motivated and they wanted to learn more after doing several gamified test with Quizizz. They were interested in elements of game such as Leaderboard, Meme, Time restriction, and Test report. Keywords: Assessment, Technology, Gamified test, Elements of game, Washback effect.